Biodiesel production from high FFA rubber seed oil using waste cockles - Zamberi, M. M. (Asian Research Publishing Network, 2016)
A two-step heterogeneous catalyzed process of high free fatty acids (FFA) rubber seed oil was conducted to produce biodiesel in lab scale. Acid esterification process was first used to reduced the high FFA rubber seed oil from 78.9% to below 1%. The low cost cockle shell was utilized as a source of CaO heterogeneous catalyst by calcination process and its effect on transesterification process was studied. The optimum yield of 88.06% was obtained for the final product of biodiesel under optimal conditions of 16:1 molar ratio of methanol to oil, 9% catalyst weight percentage with 3 hours reaction time. All fuel properties were analysed according to the ASTM D 6751 standard and found within the requirements.